Cardiac quantitative susceptibility mapping (QSM) for heart chamber oxygenation. Issue 3 (26th June 2017) - Wen, Yan; Nguyen, Thanh D.; Liu, Zhe; Spincemaille, Pascal; Zhou, Dong; Dimov, Alexey; Kee, Youngwook; Deh, Kofi; Kim, Jiwon; Weinsaft, Jonathan W.; Wang, Yi
Abstract : Purpose: To demonstrate the feasibility of in vivo quantitative susceptibility mapping (QSM) in cardiac MRI and to show that mixed‐venous oxygen saturation (SvO2 ) can be measured non‐invasively using QSM. Methods: Electrocardiographic‐gated multi‐echo 2D gradient echo data were collected at 1.5 T from 14 healthy volunteers during successive breath‐holds. Phase wraps and fat chemical shift were removed using a graph‐cut‐based phase analysis and IDEAL in an iterative approach. The large susceptibility range from air in the lungs to blood in the heart was addressed by using the preconditioning approach in the dipole field inversion. SvO2 was calculated based on the difference in blood susceptibility between the right ventricle (RV) and left ventricle (LV). Cardiac QSM quality was assessed by two independent readers. Results: Nine out of fourteen volunteers (64%) yielded interpretable cardiac QSM. QSM maps showed strong differential contrast between RV and LV blood with RV blood having higher susceptibility values (291.5 ± 32.4 ppb), which correspond to 78.3 ± 2.3% SvO2 . Conclusion: In vivo cardiac QSM is feasible and can be used to measure SvO2, but improvements in data acquisition are needed. Magn Reson Med 79:1545–1552, 2018. © 2017 International Society for Magnetic Resonance in Medicine.